2-Methoxyethanol as an alternative reaction solvent for the synthesis of 1,5-benzodiazepines under microwave irradiation - Sainath B. Zangade; Shyam Mokle; Shivaji Chavan; Yeshwant B Vibhute (Orbital: The Electronic Journal of Chemistry, 2011)
An improved condensation reaction between substituted 2’-hydroxychalcones and o-phenylenediamine using piperidine in 2-methoxyetahnol as an efficient and alternative reaction medium. The clean reaction conditions, easy work up, time saving and higher yields are notable advantages of present method.